1997
DOI: 10.1161/01.atv.17.3.547
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Osteopontin in Calcified Human Aortic Valves

Abstract: Cardiac valve calcification often results in obstruction of blood flow, which eventually leads to valve replacement. The molecular mechanisms resulting in valve calcification are unknown. Collagen and specific bone matrix proteins are thought to provide the framework for ectopic tissue calcification. This investigation was performed to determine whether the bone matrix protein osteopontin was present in calcified human aortic valves. Proteins extracted from human aortic valve tissue were subjected to polyacryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
95
1
7

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(106 citation statements)
references
References 27 publications
3
95
1
7
Order By: Relevance
“…Valvular calcium deposits contain both calcium and phosphate 11,57,63,63 as hydroxyapatite, 57,63 the form of calcium-phosphate mineral present in both calcified arterial tissue 64 and bone. Proteins involved in regulation of tissue calcification have been detected in calcified valvular tissue, including osteopontin, 13,14 bone morphogenic proteins (BMPs) 2 and 4, 15 and receptor activator of nuclear factor NF-B ligand (RANKL). 65 Osteoprotegrin (OPG), which prevents mineral resorption in bone tissue, is a soluble decoy receptor that resembles RANK and acts as a competitive inhibitor of RANK binding to RANKL.…”
Section: Calcificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Valvular calcium deposits contain both calcium and phosphate 11,57,63,63 as hydroxyapatite, 57,63 the form of calcium-phosphate mineral present in both calcified arterial tissue 64 and bone. Proteins involved in regulation of tissue calcification have been detected in calcified valvular tissue, including osteopontin, 13,14 bone morphogenic proteins (BMPs) 2 and 4, 15 and receptor activator of nuclear factor NF-B ligand (RANKL). 65 Osteoprotegrin (OPG), which prevents mineral resorption in bone tissue, is a soluble decoy receptor that resembles RANK and acts as a competitive inhibitor of RANK binding to RANKL.…”
Section: Calcificationmentioning
confidence: 99%
“…The first was the long-held notion that calcific aortic valve disease was a "degenerative," and therefore unmodifiable, condition. 6 However, more recent studies have demonstrated convincingly that calcific aortic valve lesions have many features characteristic of an active pathobiological process, including chronic inflammation, [7][8][9] lipoprotein deposition, 10 -12 active calcification, [13][14][15][16][17][18] and renin-angiotensin system activation. 19,20 These features are present in both trileaflet and bileaflet aortic valve lesions.…”
mentioning
confidence: 99%
“…OPN is a phosphorylated glycoprotein generated or secreted by osteoblasts, osteoclasts, macrophages, T cells, hematopoietic cells, VSMCs, fibroblasts, and myocardial cells [16] . In calcified human aortic valves, OPN protein expression is upregulated and colocalizes with valvular calcific deposits [17] . OPN and cMGP were found to be expressed at calcification sites within atherosclerotic lesions and in microvessels with Adrenomedullin up-regulates osteopontin and attenuates vascular calcification via the cAMP/PKA signaling pathway www.nature.com/aps Cai Y et al Acta Pharmacologica Sinica npg calciphylaxis [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular calcification is an age-linked active complex process where oxidized low-density lipoproteins, T-lymphocyte accumulation, autophagic cell death, osteoblast-like differentiation, and osteopontin producing macrophages have been shown to play major roles [11][12][13]. Recently, there has also been a paradigm shift in the understanding of pathogenesis of calcification from a passive atherosclerotic process to an actively regulated one involving activation of osteoblast cells and utilizing similar biochemical processes as in bone formation [14,15].…”
Section: Discussionmentioning
confidence: 99%